The Effectiveness of CBT Group Counseling with Stress Inoculation Training Technique to Improve Students Eustress and Life Satisfaction - Rupita, Rupita; Puji Sugiharto, Dwi Yuwono; Sunawan, Sunawan (Study Program of Guidance and Counseling, Postgraduate Program, Universitas Negeri Semarang, 2020)
The workloads students have in school make them experience eustress and low life satisfaction. Therefore, this study attempted to prove the effectiveness of CBT group counseling with stress inoculation training to improve students’ eustress and life satisfaction. Of 28 students chosen using purposive sampling technique, Pretest-Posttest Control Group Design was implemented. Their data were collected using eustress scale and life satisfaction scale. The results of repeated measures mixed manova test proved that stress inoculation training was effective to improve eustress (F (1. 26) = 485.06, p <0.01) and life satisfaction (F (1. 26) = 67.06 p <0,01). In this way, counselors should focus on coping skills in stress inoculation training, such as breathing relaxation and stress management